2017
DOI: 10.1097/md.0000000000009297
|View full text |Cite
|
Sign up to set email alerts
|

The combination assessment of lipid pool and thrombus by optical coherence tomography can predict the filter no-reflow in primary PCI for ST elevated myocardial infarction

Abstract: The usefulness of distal protection devices is still controversial. Moreover, there is no report on thrombus evaluation by using optical coherence tomography (OCT) for determining whether to use a distal protection device. The aim of the present study was to investigate the predictor of filter no-reflow (FNR) by using OCT in primary percutaneous coronary intervention (PCI) for ST-elevated acute myocardial infarction (STEMI).We performed preinterventional OCT in 25 patients with STEMI who were undergoing primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The presence of LRP in culprit lesions was reported to lead to in-stent plaque prolapse, incomplete stent apposition and edge dissection 28,31,32) . In addition, the risk of no-reflow and increment of cardiac biomarkers was also higher in patients with LRP 33,34) . In a recent study, patients with plaque erosion were shown to have poor prognosis if their underlying plaque phenotype was lipid rich 3) .…”
Section: Limitationmentioning
confidence: 93%
“…The presence of LRP in culprit lesions was reported to lead to in-stent plaque prolapse, incomplete stent apposition and edge dissection 28,31,32) . In addition, the risk of no-reflow and increment of cardiac biomarkers was also higher in patients with LRP 33,34) . In a recent study, patients with plaque erosion were shown to have poor prognosis if their underlying plaque phenotype was lipid rich 3) .…”
Section: Limitationmentioning
confidence: 93%
“…Lipid index was estimated by multiplying the lipid arc average with the length calculated longitudinally of the lipid-rich component. 20 …”
Section: Methodsmentioning
confidence: 99%
“…As OCT exhibits limited tissue penetration and is constrained by attenuation effects, however, thrombus images can become unclear, particularly for red thrombi, thus preventing thorough quantitative analyses of thrombi or underlying plaques, especially in the presence of lipid plaques or thrombus. Besides, OCT is not suited to visualization as far as the outer membrane ( Figure 2 ) ( 46 ). Kaivosoja et al ( 47 ) thus designed a novel computer image analysis-based approach to assessing thrombus morphology in OCT images.…”
Section: Non-molecular Imaging Of Thrombosismentioning
confidence: 99%